2005
DOI: 10.1051/0004-6361:20053694
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical calculations of excited rovibrational levels of HD. Term values and transition probabilities of VUV electronic bands

Abstract: In this paper, we derive the theoretical properties of rovibrational levels belonging to excited B, C, B , and D electronic states of HD. We compute the eigenvalues and eigenfunctions of the nuclear coupled Schroedinger equations using ab initio electronic molecular properties available in the literature. Transition wavenumbers and spontaneous emission probabilities are calculated for all transitions belonging to B−X, C−X, B −X, and D−X electronic band systems of HD when the upper rotational quantum number is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 29 publications
(59 reference statements)
4
35
0
Order By: Relevance
“…Another selection criterion was a high signal-to-noise ratio around the 1105.83 8 HD line. This line is 100 times weaker than the rest of the HD absorption features measured, all of which have similar oscillator strengths (HD f-values and wavelength data from Abgrall & Roueff 2006). In many cases this weak line's equivalent width is the only one falling on the linear portion of the COG, thus providing unambiguous information about the column density as Lacour et al (2005) found in their study.…”
Section: Observation and Data Reductionsupporting
confidence: 49%
“…Another selection criterion was a high signal-to-noise ratio around the 1105.83 8 HD line. This line is 100 times weaker than the rest of the HD absorption features measured, all of which have similar oscillator strengths (HD f-values and wavelength data from Abgrall & Roueff 2006). In many cases this weak line's equivalent width is the only one falling on the linear portion of the COG, thus providing unambiguous information about the column density as Lacour et al (2005) found in their study.…”
Section: Observation and Data Reductionsupporting
confidence: 49%
“…The short tick marks indicate the position of the three H 2 -bearing components, the reddest of which also features CO and HD absorptions. The origin of the velocity scale for this figure and all following ones is defined at the position of the CO-bearing component at z abs = 2.68957. and oscillator strengths were taken from Morton & Noreau (1994) and Eidelsberg & Rostas (2003) for CO and from Abgrall & Roueff (2006) for HD. Updated wavelengths of H 2 Lyman and Werner bands were taken from Bailly et al (2010), with oscillator strengths from the Meudon group 1 , based on calculations described in Abgrall et al (1994).…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] A radiative model includes the excitation by AS beams and the de-excitation by spontaneous emission ͑X 1 ⌺ g + ↔ B 1 ⌺ u + ͒ leading to a system of rate equations, which has been solved analytically. A fluorescence yield is calculated for each possible excitation taking into account the excitation rate, spontaneous and stimulated emission probabilities, optical properties of the spectrometer, and saturation effects.…”
Section: Methodsmentioning
confidence: 99%